Microscopic Numerical Analysis of Sand Liquefaction Under Subway Train Load - Jin Zhang; Jiale Yang; Chuanlong Xu; Xianzhang Ling; Chen Liu; Mohsen Saleh Asheghabadi (Applied Sciences, 2025)
Long-term vibrations from metro trains can cause liquefaction of water-rich sandy soil foundations, affecting the safety of operational tunnels. However, existing liquefaction studies mainly focus on seismic loads, and the macro-meso-mechanical mechanisms of liquefaction induced by train vibration loads remain unclear, which hinders the establishment of effective liquefaction prediction and evaluation methods. To investigate the microscopic mechanisms underlying sand liquefaction caused by train-induced vibrations, this study employs PFC3D discrete element software in conjunction with laboratory experiments to analyze the microscopic parameters of the unit cell. The findings indicate that the coordination number, mechanical coordination number, porosity, contact force chains, and strain energy all decrease with increasing vibration frequency. Conversely, the pore pressure, anisotropy, and energy exhibit opposite trends, continuing until the sample reaches a state of liquefaction failure. Notably, when the dynamic stress amplitude increases or the loading frequency decreases, the rate of reduction in coordination number, mechanical coordination number, porosity, contact force chains, and strain energy becomes more pronounced. Similarly, the rate of increase in pore pressure and anisotropy is more significant under these conditions. The research findings can provide a reference for the design of metro projects and liquefaction mitigation measures, thereby enhancing the safety and reliability of urban metro transportation systems.